2016
DOI: 10.1016/j.esxm.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Premature Ejaculation in the Anhui Male Population in China: Evidence-Based Unified Definition of Lifelong and Acquired Premature Ejaculation

Abstract: IntroductionIn 2014, new evidence-based definitions of lifelong premature ejaculation (LPE) and acquired premature ejaculation (APE) were proposed by the International Society for Sexual Medicine. Based on the new PE definitions, the prevalence of and factors associated with LPE and APE have not been investigated in China.AimTo evaluate the prevalence of and factors associated with LPE and APE in men with the complaint of PE in China.MethodsFrom December 2011 to December 2015, a cross-sectional field survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
3
14
1
Order By: Relevance
“…When compared with PE‐only patients, those with ED and PE have a higher prevalence of hypertension, diabetes, and heart diseases, more organic risk factors for sexual dysfunction (as denoted by a higher SIEDY scale 1 score), worse penile blood flows and, accordingly, a greater estimated 10‐year CV risk. This suggests that ED‐PE men should be regarded as patients at higher CV risk and not considered similar to PE‐only men, who are not usually characterized by cardio‐metabolic risk factors (Corona et al ., ; Lotti et al ., ; Gao et al ., ). Hence, in PE patients, clinicians should carefully investigate the concomitant presence of ED not only for choosing the most proper treatment, but also for identifying overall unhealthier subjects.…”
Section: Discussionmentioning
confidence: 97%
“…When compared with PE‐only patients, those with ED and PE have a higher prevalence of hypertension, diabetes, and heart diseases, more organic risk factors for sexual dysfunction (as denoted by a higher SIEDY scale 1 score), worse penile blood flows and, accordingly, a greater estimated 10‐year CV risk. This suggests that ED‐PE men should be regarded as patients at higher CV risk and not considered similar to PE‐only men, who are not usually characterized by cardio‐metabolic risk factors (Corona et al ., ; Lotti et al ., ; Gao et al ., ). Hence, in PE patients, clinicians should carefully investigate the concomitant presence of ED not only for choosing the most proper treatment, but also for identifying overall unhealthier subjects.…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon may be due to the higher percentage of APE in the IELT >1 min group because a previous study reported that patients with APE were more likely to smoke. 29 In normal men, no correlation between the penile vibratory threshold and IELT was found, and penile sensitivity cannot explain variability in IELT. 30 We validated this conclusion in the PE population by finding no difference in the penile sensory thresholds between the IELT ≤1 min and IELT >1 min groups, and there was no correlation between penile sensitivity and IELT.…”
Section: Discussionmentioning
confidence: 94%
“…Premature ejaculation is one of the common male sexual problems, with the reported prevalence rate of 20% to 30% in China. [1] Subjects with premature ejaculation would have short intravaginal ejaculatory latency time (IELT) of less than 1 min. Personal distress and interpersonal difficulty were often experienced along with ejaculatory dysfunction.…”
Section: Introductionmentioning
confidence: 99%